2018
DOI: 10.1177/1541931218621129
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Situation Awareness in Patient Flow Management: An Admission Case Study

Abstract: Managing patient flow can be an effective strategy to reduce idling hospital beds, thereby lowering the healthcare cost without sacrificing quality of care. However, improving patient flow can be a major challenge due to the complex patterns of communication across diverse hospital staff. To identify improvement opportunities, this paper investigates whether the Distributed Situation Awareness (DSA) framework can feasibly and meaningfully model Situation Awareness (SA) in patient flow. The investigation involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The DSA three-part method helped to identify functions and knowledge/SA of the CECC as well as the government ministries and agencies pertinent in their communication. Due to the lack of access to the CECC, data elicitation only involved documentation review of published articles and public video recordings rather than internal documentation review, interviews, and observations [14], [28], [29]. Data extraction involved identifying how the CECC operates (i.e., task elements), what information or SA is generated or transmitted (i.e., knowledge elements), and which ministries and agencies are involved for each operation (i.e., social elements).…”
Section: B Dsa Modelling Methodologymentioning
confidence: 99%
“…The DSA three-part method helped to identify functions and knowledge/SA of the CECC as well as the government ministries and agencies pertinent in their communication. Due to the lack of access to the CECC, data elicitation only involved documentation review of published articles and public video recordings rather than internal documentation review, interviews, and observations [14], [28], [29]. Data extraction involved identifying how the CECC operates (i.e., task elements), what information or SA is generated or transmitted (i.e., knowledge elements), and which ministries and agencies are involved for each operation (i.e., social elements).…”
Section: B Dsa Modelling Methodologymentioning
confidence: 99%
“…The DSA network model reveals the communication and coordination between agents (i.e., human and machine) and situation awareness (SA) exchange between them for patient flow management (Alhaider et al, 2020(Alhaider et al, , 2018. For example, Figure 1 presents a DSA network model depicting the room cleaning process after patient discharge.…”
Section: Dsa Network Modelmentioning
confidence: 99%
“…Previous research revealed that patient transport efficiency can be investigated with Distributed Situation Awareness (Alhaider et al, 2018(Alhaider et al, , 2020a, a theoretical framework proposed by Stanton et al (2006) for depicting the distribution and exchange of situation awareness (SA) between agents (i.e., human and machines) in complex systems. Alhaider et al, (2020a) presented a descriptive DSA network model combining social, task, and knowledge elements of patient transport to identify deficient SA transactions between agents that appeared to be associated with re-scheduling, cancelations, and delays, thereby prolonging minimum length of the patient journeys.…”
Section: Introductionmentioning
confidence: 99%